The Intrinsic Room-Temperature Ferromagnetism in ZnO:Co Thin Films Deposited by PLD - C. C. Wang; B. Y. Man; M. Liu; C. S. Chen; S. Z. Jiang; S. Y. Yang; S. C. Xu; X. G. Gao; B. Hu (Advances in Condensed Matter Physics)
c-axis preferential orientated ZnO:Co thin films were synthesized on c-plane sapphire substrates by using pulsed laser deposition (PLD) technique in an oxygen-deficient ambient. X-ray diffraction spectra, scanning electron microscopy, X-ray photoelectron spectroscopy, energy dispersive spectroscopy, UV-vis transmittance spectra, and Raman spectra were used for characterization. Ferromagnetic behavior was clearly observed at room temperature and verified to be the intrinsic property of the material. The presence of second phase was ruled out.